PENGARUH KOMUNIKASI TERHADAP UPAYA MENINGKATKAN DISIPLIN KERJA PEGAWAI PT. JAMSOSTEK (PERSERO) BANDAR LAMPUNG - Muhammad roni suaip; Hesti Widi Astuti (Institut Informatika Dan Bisnis (IIB) Darmajaya, 2015)
The Achievement of organizational goals,depends on the discipline of work,supported by the best morale and high a rousal that is the basisof success or failure of organizational purpose. The Employee discipline is strongly influenced by the ability to communicate between each element, because the discipline is closely related to the delivery of rules and sanctions that is accompanied by aprocess of coaching and supervision. This means, The delivery process that is not accompanied by the ability to communicate will result in not maximal achieved objectives. The purpose of this research is to determine whether there is a significant effect of communication on employee discipline PT. Jamsostek (Persero) Bandar Lampung. The Research used two variables, the independent variable (X) is the communication variables and the dependent variable(Y) is the discipline of work. From data analysis to prove the hypothesis, researcher found an answer that There is significant. relationship between communication variables (X) on employee discipline(Y) in PT. Jamsostek (Persero) Bandar Lampung. This is evidenced by t-coun tgreat erthan the value. oft-table. Regression calculation results obtain edt-count for communication variables (X) of 3.023is greater than the valuet-tabel2.042, meaning that communication (X) have significant effect on employee discipline(Y) in PT. Jamsostek(Persero) Bandar Lampung. Large coefficient(b) the positive value in dicates that the communication variables (X) significant effect on employee discipline (Y) in environments PT. Jamsostek (Persero). The coefficient value of0.843 means that if the communication variables (X) rose by 1 percent, the employee discipline(Y) in PT. Jamsostek(Persero) Bandar Lampung in creased by0,843 percent.Key Word : communication, discipline